1998
DOI: 10.1080/08039489850139111
|View full text |Cite
|
Sign up to set email alerts
|

Increasing fear of nuclear war among adolescents before the outbreak of the Persian Gulf War

Abstract: KARI POIKOLAINEN, RIITTA KANERVA, JOUKO LO 8 NNQVIST Poikolainen K, Kanerva K, Lö nnqvist J. Increasing fear of nuclear war among adolescents before the outbreak of the Persian Gulf War. Nord J Psychiatry 1998;52:197 -202. Oslo. ISSN 0803-9488. After the occupation of Kuwait by Iraq, tension grew in the Persian Gulf area, and war became increasingly likely until it broke out on 16 January 1991. Uncertainty about the magnitude of warfare and the possible use of nuclear, chemical, and biological weapons may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…Low self‐esteem is reported in older persons with a high prevalence of accidental falls, with this also being positively associated with a greater fear of falling . In its turn, the fear of falling is positively associated with a lower self‐esteem . Thus, the higher TDI prevalence among adolescents with low SoC and parental support could be attributed to a low self‐esteem.…”
Section: Discussionmentioning
confidence: 98%
“…Low self‐esteem is reported in older persons with a high prevalence of accidental falls, with this also being positively associated with a greater fear of falling . In its turn, the fear of falling is positively associated with a lower self‐esteem . Thus, the higher TDI prevalence among adolescents with low SoC and parental support could be attributed to a low self‐esteem.…”
Section: Discussionmentioning
confidence: 98%
“…Looking first at a high degree of meaning in life, this aspect is often closely related to being engaged in the surrounding world (see, for example, 105), which could also lead to an awareness of different societal problems, such as global environmental problems, and therefore also lead to more worry. Some research concerning worry about nuclear war also showed that those who worried the most had more positive life experiences (106). The argument was that young people who do not have more acute things to fear in everyday life have more energy left to worry about a distant problem like nuclear war.…”
Section: Negative Emotions About Global Environmental Problems and Relations To Mental Health Worry Anxiety Hopelessness And Relations Tomentioning
confidence: 99%
“…This gender difference extends to perceptions of national threat. Young Finnish women were more afraid than young men of nuclear war before the onset of the Gulf war (Poikolainen, Kanerva, & Loennqvist, 1998). Arian and Gordon (1993) found that Israeli women were more fearful than men during the Gulf war.…”
Section: Determinants Of Personal Threatmentioning
confidence: 99%